Doing Our Part to Conserve Resources: Determining Whether All Personal Protective Equipment Is Mandatory for Closed Reduction and Percutaneous Pinning of Supracondylar Humeral Fractures. (1st July 2020) - Wilson, Jacob M.; Schwartz, Andrew M.; Farley, Kevin X.; Devito, Dennis P.; Fletcher, Nicholas D.
Abstract : Background: Closed reduction and percutaneous pinning (CRPP) of supracondylar humeral fractures is one of the most common procedures performed in pediatric orthopaedics. The use of full, standard preparation and draping with standard personal protective equipment (PPE) may not be necessary during this procedure. This is of particular interest in the current climate as we face unprecedented PPE shortages due to the current COVID-19 pandemic. Methods: This is a retrospective chart review of 1, 270 patients treated with CRPP of a supracondylar humeral fracture at 2 metropolitan pediatric centers by 10 fellowship-trained pediatric orthopaedic surgeons. One surgeon in the group did not wear a mask when performing CRPP of supracondylar humeral fractures, and multiple surgeons in the group utilized a semisterile preparation technique (no sterile gown or drapes). Infectious outcomes were compared between 2 groups: full sterile preparation and semisterile preparation. We additionally analyzed a subgroup of patients who had semisterile preparation without surgeon mask use. Hospital cost data were used to estimate annual cost savings with the adoption of the semisterile technique. Results: In this study, 1, 270 patients who underwent CRPP of a supracondylar humeral fracture and met inclusion criteria were identified. There were 3 deep infections (0.24%). These infections all occurred in the group using full sterile preparation and surgical masks. No clinically relevant pin-track infections were noted. There were no known surgeon occupational exposures to bodily fluid. It is estimated that national adoption of this technique in the United States could save between 18, 612 and 22, 162 gowns and masks with costs savings of $3.7 million to $4.4 million annually. Conclusions: We currently face critical shortages of PPE due to the COVID-19 pandemic. Data from this large series suggest that a semisterile technique during CRPP of supracondylar humeral fractures is a safe practice. We anticipate that this could preserve approximately 20, 000 gowns and masks in the United States over the next year. Physicians are encouraged to reevaluate their daily practice to identify safe opportunities for resource preservation. Level of Evidence: Therapeutic Level III . See Instructions for Authors for a complete description of levels of evidence.